Minocycline inhibits rosacea-like inflammation through the TLR4-mediated NF-κB signaling pathway in vivo and in vitro - Piyan Hua; Ying Tu; Zhenghui Yang; Yunting He; Li He; Qiuyan Yao; Hua Gu (PLoS ONE, 2025)
Background Rosacea is a chronic inflammatory skin disease characterized by multiple intricate pathogenic factors. Previous studies have substantiated the anti-inflammatory properties of minocycline and its potential therapeutic efficacy in treating rosacea. However, further elucidation of the underlying mechanism is warranted. Methods HaCaT cells and BALB/c mice were treated with LL37. Moreover, the effect of minocycline on rosacea was explored through the addition of an NF-κB inhibitor (PDTC) or overexpression of Toll-like receptor 4 (TLR4). The expression of related markers was detected by western blotting, immunofluorescence, ELISA, flow cytometry, etc. Results Minocycline suppressed dermal infiltration of inflammatory cells in rosacea-like mice and reduced the expression of inflammatory cytokines in rosacea-like mice and cells. Moreover, minocycline downregulated the expression of TLR4 and p-NF-κB thereby inhibiting ROS production. However, overexpression of TLR4 or the addition of PDTC counteracted the effects of minocycline by promoting cellular inflammation and ROS production. Mechanistically, minocycline hinders TLR4/TNF-α activation induced by LL37 in skin and cells to suppress the expression of inflammatory cytokines. Conclusion Minocycline alleviates inflammation progression in rosacea by downregulating TLR4 and inhibiting the activation of the NF-κB pathway, providing a scientific basis for subsequent clinical treatment.